Psychological Intervention and Human Behavior: Insights into Effectiveness, Challenges, and Future Directions - Manikandan, R.; Barathi, C. (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Psychological interventions play a crucial role in shaping and modifying human behavior and promoting mental well-being. Whether through clinical treatments, educational support, or social programs, psychological interventions are employed to alleviate suffering, foster personal growth, and change maladaptive behaviors. This paper explores the various psychological approaches that target human behavior, highlights the impact of these interventions across different settings, and discusses the challenges, limitations, and ethical considerations involved. Through a synthesis of contemporary research and practical examples, the paper aims to offer insights into how psychological interventions can be optimized to promote positive behavioral outcomes across diverse populations and contexts.